Cytokine production and signaling pathways in respiratory virus infection - Kimura, Hirokazu (Frontiers Media S.A., 2013)
It has been confirmed that respiratory virus infections can induce abberant cytokine production in the host. These cytokines may be associated with both elimination of the virus and complications in the host, such as virus-induced asthma. Representative host defense mechanisms against pathogens, including bacteria and viruses, are mediated by the innate immune system. Cells of the innate immune system express essential molecules, namely pattern recognition receptors (PRRs), such as Toll-like receptors, nucleotide-binding oligomerization domain-like receptors, and retinoic acid-inducible gene-I-like receptors. These PRRs can recognize components of pathogens such as bacterial lipopolysaccharide, viral antigens, and their genomes (DNA and RNA). Furthermore, PRRs activate various signaling pathways resulting in cytokine production against pathogen infection. However, the exact mechanisms remain unknown. In this review, we mainly focus on the representative mechanisms of cytokine production through PRRs and signaling pathways due to virus infections, including respiratory virus infections. In addition, we describe the relationships between respiratory infections and virus-induced asthma.